2020
DOI: 10.1002/alz.12161
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between memory decline and the use of metformin or DPP4 inhibitors in people with type 2 diabetes with normal cognition or Alzheimer's disease, and the role APOE carrier status

Abstract: Introduction: Few studies have examined memory decline among patients with type 2 diabetes using different oral hypoglycemic drugs. Methods: Participants with normal cognition (NC) or Alzheimer's disease (AD) dementia using a hypoglycemic medication (2005 to 2019) were identified from the National Alzheimer's Coordinating Center database. Delayed memory was assessed using the Wechsler Memory Scale Revised-Logical Memory test. Associations between oral This is an open access article under the terms of the Creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 52 publications
5
52
1
Order By: Relevance
“…Specifically, we observed that before starting the MedDiet intervention, individuals with type 2 diabetes from a group presenting good glycemic control (S1) treated with metformin presented a higher performance in memory, executive functions and global cognition than those not treated with metformin. These results agree with previous observational studies showing better memory performance (14) or greater maintenance of executive functions and global cognition (34) in cognitively normal subjects with diabetes type 2 treated with metformin, compared to those not treated with metformin. Metformin use has also been associated with lower dementia risk (35,36) and better cognitive function (37), but results are still highly variable across studies (15).…”
Section: Metformin Use and Cognition In Individuals With Diabetessupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, we observed that before starting the MedDiet intervention, individuals with type 2 diabetes from a group presenting good glycemic control (S1) treated with metformin presented a higher performance in memory, executive functions and global cognition than those not treated with metformin. These results agree with previous observational studies showing better memory performance (14) or greater maintenance of executive functions and global cognition (34) in cognitively normal subjects with diabetes type 2 treated with metformin, compared to those not treated with metformin. Metformin use has also been associated with lower dementia risk (35,36) and better cognitive function (37), but results are still highly variable across studies (15).…”
Section: Metformin Use and Cognition In Individuals With Diabetessupporting
confidence: 92%
“…This approach allows to account for systematic differences in comorbidities between groups and is used to limit confounding by indication. We also had no information about the APOE genotype of participants, which could influence the association between metformin use and cognitive decline, as reported in previous studies (14).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort data from National Alzheimer's Coordinating Center suggests that the association between metformin use and better memory performance overtime is only observed in diabetic patients with normal cognition (n 1192). By comparison, in patients with AD (n 807), dipeptidyl peptidase-4 inhibitor treatment is associated with a slower memory decline (Wu et al, 2020). In a pooled study including five population-based cohorts (3,590 individuals with diabetes), no significant associations are found between metformin use and brain function and structure outcomes (Weinstein et al, 2019).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…It was confirmed in a more recent study that type-2 diabetes did not correlate with the amyloid plaque or neurofibrillary tangle load, but it was commented on that both diseases are associated at early stages with a significant cerebrovascular disease that can affect the development of AD pathology [ 27 ]. Much interest in this topic has been on whether patients treated with the insulin sensitizer metformin have a reduced risk of dementia [ 137 , 138 , 139 ]. Metformin, which activates AMPK leading to inhibition of TXNIP expression, has significant activity in inhibiting the activation of the NLRP3 inflammasome complex [ 140 , 141 , 142 ].…”
Section: Txnip Expression In the Brainmentioning
confidence: 99%